Annual Plan Proposals 1972-73 Government of Kerala Department of Planning and Economic Affairs - Planning Commission (Planning Commission, 1971)
The Annual Plan Proposals for 1972-73 have been prepared in accordance with the instructions contained in letter No. PC(B) 2/71 dated 31-8-1971 from the Planning Commission. The outlay proposed for 1972-73 in the State Sector is Rs. 70.77 crores. A provision of Rs. 10.89 crores is included to meet the expenditure on Centrally Sponsored Schemes. Thus the gross Plan Outlay during 1972-73 will be Rs. 81.66 crores. While drawing up proposals, priority has been given to (a) schemes to which Government are committed (b) spill-over and incomplete schemes (c) completion of schemes which are advanced and (d) full utilisation of the capacities created by Plan investment in the past years. The proposals for 1972-73 have been made on the basis of the minimum requirements under each and every head. The Committee on Unemployment, has drawn up proposals for an investment of Rs. 186 crores.
Government of Kerala Department of Planning and Economic Affairs